157: Evaluation of the Canadian Pediatric Society's Global Health Education Modules. Issue 6 (1st June 2014) - Kay, S; Hunter, AJ; Audcent, T
Abstract: BACKGROUND: Training in global health topics is increasingly recognized as an important element of pediatric residency. The Canadian Pediatric Society's (CPS) Global Child and Youth Health Section created a set of four modules to serve as a national curriculum on global health for pediatric residents. The topics of the modules include global child mortality, undernutrition, fever in a returning traveler, and children new to Canada. The modules are available free online for CPS members or by mail order CD (at cost). OBJECTIVES: To identify the uptake of the modules in order to understand their utilization and to identify areas for improvement and expansion. DESIGN/METHODS: An online survey was distributed to medical educators who underwent module training, requested use of the modules, or ordered them online from the CPS. The survey was used to elicit information regarding the implementation of the modules, feedback on their content and the perceived impact on residents. Descriptive statistics were used to tabulate close-ended responses in aggregate format. All open-ended responses were analyzed using content analysis and key themes were extracted, summarized, and reported. Ethics approval was granted by the McMaster University ethics board. RESULTS: Forty-nine pediatricians were invited to participate in the survey. Forty-four percent (22) completed the survey including 17 from Canadian programs and five from the United States, with 67% of Canadian academic centres represented. The majority of respondents were hospitalist pediatricians (89.5%) working in an academic centre (95%) who had an interest in global health (82%). Forty percent (nine) were involved in the creation of the modules. Only 35% attended the training workshop on the modules and the remainder prepared by reading through the training materials provided. The main forum for the modules was pediatric academic half-day (79%); although, a few individuals used them at conferences and as part of pre-departure training for global health electives. Module content received positive ratings overall: 87% indicated they were well received by the residents, 94% indicated knowledge expansion, and 89% would recommend them to colleagues. The main concern identified was keeping the modules updated. Other notable feedback suggested residents appreciated opportunities within the presentation to apply their knowledge. While there are additional resources available for the modules, only some participants utilized them; including pre-tests (45%), post-tests (32%) observed structural clinical encounters (36%), and resident handouts (59%). CONCLUSIONS: These modules received positive responses from pediatric educators with an interest in global health, including among those unable to attend the training session. Future directions include further module dissemination, updating the current modules and creating new ones.